Assessing the Efficacy of Government Floor Price Interventions in Stabilizing Farm Gate Paddy Prices Across Major Indonesian Production Hubs - Sulistyaningsih; Titik ismandari; Alfath Desita Jumiar; Nurlaila (CV. HEI PUBLISHING INDONESIA, 2026)
This study evaluates the effectiveness of the Government Purchase Price (HPP) policy in stabilizing farm-gate paddy prices in major rice-producing regions of Indonesia. Monthly panel data from the Central Bureau of Statistics and the National Food Agency for 2020–2025 were analyzed using descriptive statistics and price parity approaches. The results indicate that HPP serves as an important price protection instrument, but its implementation remains uneven due to logistical constraints and limited post-harvest infrastructure. In South Sulawesi, farm-gate prices were consistently around 150 IDR/kg below the HPP benchmark, while regression analysis revealed a negative relationship between grain moisture content and compliance with HPP standards (β = -0.456). The findings suggest that the effectiveness of the floor price policy depends not only on the established price level, but also on procurement capacity and post-harvest quality management. Therefore, region-specific pricing strategies and investment in drying facilities are necessary to improve farmer welfare and strengthen food price stability in Indonesia.